Cost-benefit of serum pepsinogen screening for gastric adenocarcinoma in the Mexican population - L.B. Enríquez-Sánchez; L.G. Gallegos-Portillo; J. Camarillo-Cisneros; M. Cisneros-Castolo; J.J. Montelongo-Santiesteban; D.A. Aguirre-Baca; A.I. Pérez-Echavarría; A.E. Contreras-Pacheco (Revista de Gastroenterología de México (English Edition), 2022)
Introduction and aim: Helicobacter pylori (H. pylori) is known to be capable of causing chronic inflammation of the gastric mucosa that slowly progresses through the premalignant stages, reaching localized gastric adenocarcinoma (GAC). Its outcome is closely related to the stage at which diagnosis is made. The aim of the present study was to determine cost-benefit by comparing esophagogastroduodenoscopy, serum pepsinogen detection, and no screening at all. Material and methods: Utilizing Markov chains and Monte Carlo simulation, the costs and effects of various detection modalities were simulated to analyze the cost-benefit of each strategy. For our population, we used the published data of patients with gastric cancer, applicable to the Mexican population. Results: The results were reported as incremental cost-effectiveness ratios. The best strategy was serum pepsinogen determination, followed by the strategy of endoscopic examination with continued monitoring every 3 years. Conclusions: The performance of serum pepsinogen serology and directed endoscopic examination (and continued monitoring, if necessary) for GAC screening could be a cost-effective intervention in Mexico, despite the low-to-moderate general prevalence of the disease. Resumen: Introducción y objetivo: Se sabe que Helicobacter pylori (H. pylori) es capaz de provocar inflamación crónica de la mucosa gástrica, que progresa lentamente a través de las etapas premalignas hasta llegar al adenocarcinoma gástrico (ACG) localizado, su pronóstico está estrechamente relacionado con la etapa en la que realiza el diagnóstico. El propósito de este estudio es determinar el costo-beneficio mediante la comparación de la esofagogastroduodenoscopia, la detección de pepsinógeno en suero o no realizar ningún cribado. Material y métodos: Utilizando cadenas de Markov y simulación de Monte Carlo se simularon los costos y los efectos de varias modalidades de detección para analizar el costo-beneficio obtenido de cada una. Para nuestra población, utilizamos los datos publicados de pacientes con cáncer gástrico, aplicables a la población mexicana. Resultados: Los resultados se informaron en proporciones incrementales de costo-efectividad (ICER). La mejor estrategia fue buscar pepsinógeno en suero, seguido de una prueba de estrategia de examen endoscópico con vigilancia continua cada 3 años. Conclusiones: La detección de pepsinógeno en suero, así como la detección endoscópica dirigida (y la vigilancia continua, si es necesario) para el cribado de ACG podría ser una intervención rentable en México a pesar de una prevalencia general de la enfermedad de baja a moderada.